The Process Of Rainfall From The Perspective Of Tafsir Ilmi By The Kemenag RI And Science - Fatnur, M. Ardi; Achmad Abu Bakar; Muhammad Irham; Dina Arbiyah (PT ARRUS Intelektual Indonesia, 2025)
This study discusses the process of rainfall from the perspective of Tafsir Ilmi by the Ministry of Religious Affairs of the Republic of Indonesia (Kemenag RI) and its scientific implications. Introduction highlights the crucial role of rain in maintaining ecosystem balance and supporting life on Earth, serving as a primary source of clean water for various human activities, from dally consumption to agriculture. Without rain, life on this planet would be threatened, as water is essential for all living beings. Rain not only provides the necessary moisture for plant growth but also contributes to the replenishment of groundwater and surface water resources while regulating climate and temperature. Method involves a qualitative descriptive approach based on literature review, collecting data from primary sources such as Tafsir Ilmi Kemenag RI and secondary sources like books and scientific articles discussing the water cycle and relevant Quranic verses. Results and Discussion reveal that the process of rainfall involves three main stages: evaporation, condensation, and precipitation, which can be explained both scientifically and through Quranic teachings. Verses such as QS. An-Nur (24:43) and QS. Ar-Rum (30:48) illustrate how Allah directs clouds and utilizes wind to create rain, emphasizing the harmony between natural laws and divine will. Conclusion asserts that Tafsir Ilmi Kemenag RI plays a vital role in bridging the understanding between science and religion, allowing society to appreciate rain not just as a physical phenomenon but also as a manifestation of God's mercy that should be valued and